2013
DOI: 10.1121/1.4800179
|View full text |Cite
|
Sign up to set email alerts
|

Preboundary lengthening and preaccentual shortening across syllables in a trisyllabic word in English

Abstract: This study demonstrates some new aspects of preboundary lengthening and preaccentual shortening on a test word banana in American English. Preboundary lengthening was found to be extended to the initial unstressed syllable beyond the main-stressed syllable, presenting more complexity than has previously been assumed. Preaccentual shortening was observed regardless of boundary strength or the stress pattern (trochaic vs iambic) of the following context word, suggesting that it operates globally at an utterance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 14 publications
2
9
0
1
Order By: Relevance
“…Another stress-related durational effect might be leakage of final lengthening to an IP-penultimate stressed syllable, as has been found for Dutch in words ending in a syllable with schwa (Cambier-Langeveld 2000: 50). Such effects have also been found for English (Shattuck-Hufnagel & Turk 1998, Cho et al 2013. A comparison of the penultimate syllable in Ambonese Malay IP-final words with the same syllable in IP-medial words failed to reveal any leakage of final lengthening to the penultimate syllable, as can be seen in Fig.…”
Section: A: Bsupporting
confidence: 67%
“…Another stress-related durational effect might be leakage of final lengthening to an IP-penultimate stressed syllable, as has been found for Dutch in words ending in a syllable with schwa (Cambier-Langeveld 2000: 50). Such effects have also been found for English (Shattuck-Hufnagel & Turk 1998, Cho et al 2013. A comparison of the penultimate syllable in Ambonese Malay IP-final words with the same syllable in IP-medial words failed to reveal any leakage of final lengthening to the penultimate syllable, as can be seen in Fig.…”
Section: A: Bsupporting
confidence: 67%
“…4 It has also been argued that prominence and phrasing have similar functions cross-linguistically [5,6,9,22,70]. The current discussion is limited to the interaction of boundary and prominence in the pre-boundary domain, as the relationship between the two phenomena has been less examined in the post-boundary domain (but see [15,71]).…”
Section: (C) the Coordination Of Prosodic Eventsmentioning
confidence: 99%
“…For example, while preboundary lengthening in English is generally observed in a final syllable or a final rhyme of a phrase‐final word (e.g., Klatt ; Edwards et al ; Wightman et al ; Byrd and Saltzman ), a recent paper by Turk and Shattuck‐Hufnagel () showed multiple targets of preboundary lengthening: the final syllable and the stressed non‐final antepenultimate syllable, indicating that preboundary lengthening may skip the intervening penultimate unstressed syllable and be extended to a stressed antepenultimate syllable (e.g., Michigan ). A small‐scaled recent paper by Cho, Kim, and Kim () showed that the effect can be extended even beyond the non‐final stressed syllable to the initial unstressed syllable in the trisyllabic test word banana . A similar interaction of preboundary lengthening with stress is found in other languages but in a language‐specific way.…”
Section: Preboundary Lengtheningmentioning
confidence: 99%